(untitled) (The Research of Medical Science Review, 2025)
The primary aim of this study is to validate an indigenous scale for assessing pathological narcissism, developed by Fatima and Naz (2023), within a clinical population. A sample of 150 in-patients aged 19–40 years (M = 28.38, SD = 6.09) was recruited from government and semi-government hospitals in Lahore, all scoring high on the FFNI-SSF. The scale underwent comprehensive evaluation, including Confirmatory Factor Analysis (CFA), test-retest reliability, and criterion validity assessments. Findings suggest that this scale is a robust tool for evaluating pathological narcissism within Pakistan’s clinical context. The CFA was conducted on a hypothesized model comprising 24 items across five factors identified in exploratory factor analysis. Incorporating covariance within the same factors significantly improved model fit, as evidenced by the Chi-square Goodness of Fit results. The model demonstrated strong statistical performance, with Goodness of Fit indices of CFI = .92, TLI = .89, RMSEA = .07, and TLI = .79. Additionally, all factors showed strong intercorrelations, confirming the scale’s convergent and divergent validity. Reliability analyses further affirmed the scale’s robustness, with both the overall scale and its subscales achieving high internal consistency (Cronbach’s alpha > .8). Test-retest reliability was also strong (r = .85). To enhance interpretability, percentile ranks were established, categorizing scores into low risk (25th percentile), moderate risk (50th percentile), and high risk (75th percentile). A cut-off score of 104, two standard deviations above the mean, was determined for identifying clinically significant pathological narcissism. This indigenous scale holds significant clinical utility, as it emphasizes the pathological dimensions of narcissism, particularly the vulnerable traits often observed in clinical populations. Its application can aid in diagnosis and intervention strategies within therapeutic settings.